Pengalaman Psikososial Penderita Systemic Lupus Erythematosus: A Systematic Review - Sahrir Ramadhan; Tintin Sukartini; Ferry Efendi (FORIKES, 2021)
Background: Systemic lupus erythematosus usually affects many organ systems including the central nervous system. So that it can cause several neuropsychiatric syndromes, including depression. In addition, lupus patients also experience frustration and social stress such as loss of the ability to work which results in unemployment resulting in reduced income from lupus sufferers and limitations in social interactions which are also major problems. Objective: to determine the psychosocial experiences of people with systemic lupus erythematosus. Methods: The databases used in this study were Scopus and Proquest, limited to publications for the last 15 years from 2005 to 2020, full text articles and in English. The keywords used are